Application of acupuncture in ophthalmological affections - Piñeiro Linares, Amanda; Rodríguez Borges, Gema; Carrión Chacón, Aneydis (Revista Científica Estudiantil UNIMED, 2020)
Acupuncture is the insertion of thin needles into the skin, more than four hundred acupuncture points have been described, with the majority located on one of the main meridians, pathways which runs throughout the body and according to Traditional Chinese Medicine (TCM) transports life energy. Chinese ophthalmology is part of the TCM, here diseases of the eyes are treated with Chinese herbs, acupuncture/moxibustion and others. A thorough review of several sources of information was carried out with the aim of describing the advantages of the use of acupuncture in the treatment of ophthalmological affections. An amount of 27 bibliographies were analyzed, concluding that the use of the acupuncture for the treatment of the ophthalmological affections has demonstrated to be an effective method and less invasive.